An integral perspective of canonical cigarette and e-cigarette-related cardiovascular toxicity based on the adverse outcome pathway framework - Ruiyang Ding; Xiaoke Ren; Qinglin Sun; Zhiwei Sun; Junchao Duan (Journal of Advanced Research, 2023)
Background: Nowadays, cigarette smoking remains the leading cause of chronic disease and premature death, especially cardiovascular disease. As an emerging tobacco product, e-cigarettes have been advocated as alternatives to canonical cigarettes, and thus may be an aid to promote smoking cessation. However, recent studies indicated that e-cigarettes should not be completely harmless to the cardiovascular system. Aim of Review: This review aimed to build up an integral perspective of cigarettes and e-cigarettes-related cardiovascular toxicity. Key Scientific Concepts of Review: This review adopted the adverse outcome pathway (AOP) framework as a pivotal tool and aimed to elucidate the association between the molecular initiating events (MIEs) induced by cigarette and e-cigarette exposure to the cardiovascular adverse outcome. Since the excessive generation of reactive oxygen species (ROS) has been widely approved to play a critical role in cigarette smoke-related CVD and may also be involved in e-cigarette-induced toxic effects, the ROS overproduction and subsequent oxidative stress are regarded as essential parts of this framework. As far as we know, this should be the first AOP framework focusing on cigarette and e-cigarette-related cardiovascular toxicity, and we hope our work to be a guide in exploring the biomarkers and novel therapies for cardiovascular injury.